THE COMPARISON OF GROUP INVESTIGATION AND THINK PAIR SHARE WITH ASSESSMENT FOR LEARNING VIEWED FROM STUDENTS’ SELF CONFIDENCE OF EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Ummu Salamah; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Proceedings Education and Language International Conference, 2017)
This research was a quasi-experimental research with a factorial design 2×3 aims to determine the comparison of Group Investigation (GI) with Assessment for Learning (AfL) through peer-assessment (GI-AfL-Peer) and TPS with AfL through peer-assessment (TPS-AfL-Peer) viewed from self confidence for student’s achievement in mathematics. The population of this research were all of Junior High School students 8th grade in Karanganyar Regency schools in academic year 2016/2017. Research samples obtained by stratified cluster random sampling. The data was collected by using methods of documentation, students’ self confidence questionnaires, and mathematics achievement test. Data analysis technique used two way analysis of variance (ANOVA) with unequal cell. According to research result, it could be concluded that: (1) students’ mathematics achievement which applied GI-AfL-Peer better than TPS-AfL-Peer, (2) mathematics achievement of students with high self confidence better than students’ with medium and low self confidence, and mathematics achievement of students’ with medium self confidence as good as students with low self confidence, (3) in each category of self confidence, students’ mathematics achievement which applied GI-AfL-Peer better than TPS-AfL-Peer, (4) in each learning model, mathematics achievement of students with high self confidence better than students’ with medium and low self confidence, and mathematics achievement of students’ with medium self confidence as good as students with low self confidence.Keywords: AfL, GI, peer-assessment, self confidence, students’ mathematics achievement, TPS